Acidity and Cd2+ fluorescent sensing and selective CO2 adsorption by a water-stable Eu-MOF. Issue 14 (12th March 2019) - Liao, Wei-Ming; Wei, Mei-Juan; Mo, Jun-Ting; Fu, Peng-Yan; Fan, Ya-Nan; Pan, Mei; Su, Cheng-Yong
Abstract : A new luminescent Eu-MOF from an amino-group modified tetracarboxylic acid ligand was designed, which could perform as an efficient pH acidity and Cd 2+ PL sensor and CO2 selector. Abstract : A new Eu-MOF was designed from an amino-functionalized ligand and Eu(iii ) ions under solvothermal conditions. It is a highly porous, water-stable, and luminescent material, exhibiting pH sensing in the acidic range of pH = 7–3 with selective detection for Cd 2+ by an enhanced fluorescence of ∼23-fold against a series of metal ions. Gas adsorption performance shows that Eu-MOF exhibits a high CO2 /N2 (15/85) selectivity of 109.4 at 273 K and 1 atm. This performance was superior to that of most reported Ln-MOFs owing to its appropriate pore size, dipole–dipole interaction and donor–acceptor Lewis affinities.